2021
DOI: 10.11002/kjfp.2021.28.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gelling agents and sugar substitutes on the quality characteristics of carrot jelly

Abstract: In this study, the quality characteristics of carrot jellies prepared using different gelling agents (gelatin and carrageenan) and sugar substitutes (sucrose, sorbitol, and xylitol) were evaluated. The effects of gelling agents and sugar substitutes on the pH, °Brix, color, syneresis, melting-down rate, textural properties, and sensory acceptance of the jellies were determined. Textural analysis indicated that gelatin-based jellies containing sugar substitutes sorbitol and xylitol showed higher hardness than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
1
0
2
Order By: Relevance
“…The hygroscopicity of xylitol to retain water and the ability to reduce water activity (free water) in pectin gels can reduce syneresis [56]. The syneresis percentage results obtained in this study correspond to research by [57]. In that study, the use of xylitol in carrot jelly reduced syneresis.…”
Section: The Effects Of Fructo-oligosaccharides and Xylitol On The Ph...supporting
confidence: 80%
“…The hygroscopicity of xylitol to retain water and the ability to reduce water activity (free water) in pectin gels can reduce syneresis [56]. The syneresis percentage results obtained in this study correspond to research by [57]. In that study, the use of xylitol in carrot jelly reduced syneresis.…”
Section: The Effects Of Fructo-oligosaccharides and Xylitol On The Ph...supporting
confidence: 80%
“…Reconstitution at 50°C revealed that 2% carrageenan produced a stable yoghurt product with no visible syneresis for hours, indicating a promising application in the production of long-life yoghurt powder ( Pratama et al, 2018 ). Confectionery jellies containing 1.5% (w/v) carrageenan demonstrated greater hardness, chewiness, cohesiveness, and syneresis, as well as lower melting rates, than gelatin-based jellies ( Park et al, 2021 ). Furthermore, carrageenans aid in the formation of gels and the retention of moisture in meat products, which is especially appealing in low-fat meats because fat reduction frequently results in undesirable, tough textures ( Trius et al, 1996 ).…”
Section: Carrageenan In Food and Medical Applicationsmentioning
confidence: 96%
“…Penurunan persen sineresis disebabkan jejaring polimer semakin rapat seiring dengan peningkatan konsentrasi gelling agent. Hal ini menyebabkan kemampuan chewable gummy dalam menahan molekul air semakin kuat [31].…”
Section: Sineresis Chewable Gummy Daun Kelorunclassified
“…Chewable gummy dengan gelling agent kappa karagenan menunjukkan persen sineresis yang lebih tinggi dibandingkan konjak glukomanan. Kappa kara-genan membentuk gel yang kaku namun rapuh, sehingga molekul air mudah bergerak menuju permukaan chewable gummy [31].…”
Section: Sineresis Chewable Gummy Daun Kelorunclassified